2232. Zinc deficiency and advanced liver fibrosis among HIV/HCV co-infected persons in Russia. (26th November 2018) - Barocas, Joshua; So-Armah, Kaku; Cheng, Debbie; Lioznov, Dmitry; Baum, Marianna; Gallagher, Kerrin; Fuster, Daniel; Gnatienko, Natalia; Krupitsky, Evgeny; Freiberg, Matthew; Samet, Jeffrey
Abstract: Background: Liver disease in people living with HIV (PLWH) co-infected with hepatitis C virus (HCV) is a common cause of non-AIDS-related death in Russia. HIV accelerates liver fibrosis in the setting of HCV co-infection thus PLWH have increased risk of cirrhosis, hepatocellular carcinoma, and liver-related mortality. Injection drug use is common among Russian PLWH and zinc deficiency is common among PLWH and people who inject drugs. We hypothesize that zinc deficiency facilitates the underlying mechanisms of liver fibrosis. We investigated the association between zinc deficiency and advanced liver fibrosis (ALF) in a cohort of HIV/HCV co-infected persons in Russia. Methods: Anti-retroviral naïve HIV-infected Russians with a recent history of heavy drinking were recruited into a clinical trial of zinc supplementation. A subset of participants ( N = 204) were HCV co-infected (qualitative HCV RNA positive) at baseline. The primary dependent variable in this cross-sectional study was advanced liver fibrosis defined as either (1) FIB-4 >3.25, (2) FIB-4 ≥1.45 or ≤3.25 with elastography suggestive of ALF (≥10.5 kPa), or (3) APRI ≥1.5. Zinc deficiency, the main independent variable, measured at baseline, was defined as <0.75 mg/L for the primary analysis. In secondary analyses, zinc level was categorized into tertiles. Analyses were conducted using multivariable logistic regression adjusted for potential confounders: demographics including BMI, HIV-related factors, and substance use including alcohol and cocaine. Results: Participant characteristics were: 33 years [median age]; 25% female; 25% with ALF, and 42% injection drug use in the past 30 days. Among those with zinc deficiency ( N = 65) compared with those with normal zinc levels ( n = 139), the prevalence of ALF was similar (27.7% vs. 23.0%, respectively). We did not detect an association between zinc deficiency and ALF in the adjusted regression model (aOR: 1.28, 95% CI: 0.62–2.61, P = 0.51). No significant association between zinc deficiency and ALF was found in secondary analyses. Of the covariates, CD4 count <350 cells/μL was significantly associated with ALF (aOR: 2.2, 95% CI: 1.05–4.62, P = 0.04). Conclusion: In this cohort of HIV/HCV co-infected Russians, we did not detect an association between zinc deficiency or zinc levels and advanced liver fibrosis. Disclosures: All authors: No reported disclosures.